Modeling of icrh slow wave propagation and absorption in Wendelstein 7-X stellarator - Grekov, D.; Turkin, Yu. (Вопросы атомной науки и техники, 2021)
The propagation and absorption of slow waves in the plasma of the Wendelstein 7-X stellarator was investigated by the ray tracing. The aim of the work was to obtain a qualitative picture of the penetration into the plasma of a wave excited by the potential difference between the antenna conductors and the antenna box. For this, a ray code was used, which performs calculations in the magnetic configuration of the stellarator obtained by the VMEC code. A strong influence of the type of magnetic configuration (“higher mirror”, “lower mirror”, or standard configuration) on the propagation and absorption of a slow wave was found. Поширення і поглинання повільної хвилі в плазмі стеларатора Вендельштейн 7-Х було досліджено методом променевих траєкторій. Мета роботи – отримання якісної картини проникнення в плазму хвилі, що збуджується за рахунок різниці потенціалів між провідниками антени і антенним боксом. Для цього використаний променевий код, який виконував розрахунки в магнітній конфігурації стеларатора, що отримана кодом VMEC. Виявлено сильний вплив виду магнітної конфігурації (посилені гофри, зменшені гофри або стандартна конфігурація) на поширення і поглинання повільної хвилі. Распространение и поглощение медленной волны в плазме стелларатора Вендельштейн 7-Х было исследовано методом лучевых траекторий. Цель работы – получение качественной картины проникновения в плазму волны, возбуждаемой за счет разности потенциалов между проводниками антенны и антенным боксом. Для этого использован лучевой код, который выполнял расчеты в магнитной конфигурации стелларатора, полученной кодом VMEC. Обнаружено сильное влияние вида магнитной конфигурации (усиленные гофры, уменьшенные гофры или стандартная конфигурация) на распространение и поглощение медленной волны.